Increased NTPDase Activity in Lymphocytes during Experimental Sepsis - Claudia de Mello Bertoncheli; Carine Eloise Prestes Zimmermann; Jeandre Augusto dos Santos Jaques; Cláudio Alberto Martins Leal; Jader Betsch Ruchel; Bruna Cipolatto Rocha; Kelly de Vargas Pinheiro; Viviane do Carmo Gonçalves Souza; Daniel Roulim Stainki; Sônia Cristina Almeida Luz; Maria Rosa Chitolina Schetinger; Daniela Bitencourt Rosa Leal (The Scientific World Journal)
We investigated in rats induced to sepsis the activity of ectonucleoside triphosphate diphosphohydrolase (NTPDase; CD39; E.C. 3.6.1.5), an enzyme involved in the modulation of immune responses. After 12 hours of surgery, lymphocytes were isolated from blood and NTPDase activity was determined. It was also performed the histology of kidney, liver, and lung. The results demonstrated an increase in the hydrolysis of adenosine-5′-triphosphate (ATP) (P<0.01), but no changes regarding adenosine-5′-monophosphate (ADP) hydrolysis (P>0.05). Histological analysis showed several morphological changes in the septic group, such as vascular congestion, necrosis, and infiltration of mononuclear cells. It is known that the intracellular milieu contains much more ATP nucleotides than the extracellular. In this context, the increased ATPasic activity was probably induced as a dynamic response to clean up the elevated ATP levels resulting from cellular death.